Health Communication and Inter-professional Care in Context of Multimorbidity Management: Assessment of Health Professional Curricular Focus in India - Pati, Sanghamitra; Sinha, Rajeshwari; Mahapatra, Pranab (Frontiers in Communication, 2021)
To meet the long term care demands of chronic diseases as well as multimorbidity, healthcare providers from different disciplines need to work collaboratively in practice. This requires healthcare providers to be appropriately trained on delivery of inter-professional care (IPC) and health communication aspects during formative professional years. In this study, we have looked at the prevailing undergraduate and postgraduate healthcare professional curricula to understand the focus on health communication and on IPC for the delivery of multidisciplinary care for multimorbidity management. We observe that while there are exclusive courses on health communication being delivered at different levels, the focus on IPC is still in stages of infancy. The IPC component is just beginning to be woven into the health professional curricula through elements like competency-based curriculum, rotational posting, inter-departmental engagements. At the same time, the need to put curricular attention on multimorbidity is also highlighted here. There remains wider scope for strengthening learning on health communication and IPC among different disciplines within the curricula in the context of multimorbidity. We expect our findings to provide key inputs to academic planners and policy makers towards the introduction of adequate curricular components for addressing multimorbidity along with necessary prescriptions for health communication and IPC in India.